Karakterisasi Simplisia Daun Tin (Ficus Carica L.) - Devi Revita Amlia; Siti Hazar (Jurnal Riset Farmasi, 2022)
Abstract. Tin leaves (Ficus carica L.) one of the creations of Allah SWT have various benefits that can be used by humans such as foodstuffs, medicine, textiles, medicinal materials, and cosmetic ingredients. Therefore Allah Almighty shows that His creations both on earth and in the crosshairs are not in vain. As in the Qur'an surah Al-Imran verses 190 to 191, based on this verse when associated with our research as His people, learning can be carried out so as to obtain benefits such as the plants created. The tin plant (Ficus carica L) belongs to the family Moraceae. The benefits of the tin plant have such effects as antibacterial, antiviral, antifungal, anticancer, antimicrobial, antioxidant and immunomodulatory. The chemical content of the leaves of Ficus carica L contains phenolics, flavonoids, alkaloids and saponins. Standardization of Tin leaf simplisia (Ficus carica L.) is carried out water content tests, water soluble juice content tests, ethanol soluble juice content, and drying shrinkage to determine the moisture content in tin leaves and the amount of compound content in simplisia that can be attracted by solvents. The method used in this study was experimental in the Laboratory of the Islamic University of Bandung. Based on the results of the standardization of Tin fruit simplisia (Ficus carica L.), a moisture content of 5%, a water-soluble juice content of 8.51%, an ethanol soluble juice content of 14.56%, and a drying shrinkage content of 3.6817% were obtained. Abstrak. Daun Tin (Ficus carica L.) salah satu ciptaan Allah SWT memiliki berbagai manfaat yang dapat digunakan oleh manusia seperti bahan makanan, obat, tekstil, bahan obat, dan bahan kosmetik. Oleh karena itu Allah SWT menunjukkan bahwa ciptaan-Nya baik dibumi dan dilangit tidak sia-sia. Sebagaimana dalam Qur’an surah Al-Imran ayat 190 sampai 191, berdasarkan ayat tersebut bila dikaitkan dengan penelitian kita sebagai umat-Nya dapat dilakukan pembelajaran sehingga memperoleh manfaat seperti tumbuhan-tumbuhan yang diciptakan. Tanaman tin (Ficus carica L) termasuk keluarga Moraceae. Manfaat dari tanaman tin memiliki efek seperti antibakteri, antiviral, antifungal, antikanker, antimikroba, antioksidan, dan imunomodulator. Kandungan kimia daun Ficus carica L mengandung fenolik, flavonoid, alkaloid, dan saponin. Standardisasi simplisia daun Tin (Ficus carica L.) dilakukan uji kadar air, uji kadar sari larut air, kadar sari larut etanol, dan susut pengeringan untuk mengetahui kadar air di dalam daun tin dan jumlah kandungan senyawa dalam simplisia yang dapat tertarik oleh pelarut. Metode yang digunakan pada penelitian ini adalah secara eksperimental di Laboratorium Universitas Islam Bandung. Berdasarkan hasil standardisasi simplisia buah Tin (Ficus carica L.) maka diperoleh kadar air sebesar 5%, kadar sari larut air sebesar 8,51%, kadar sari larut etanol sebesar 14,56%, dan kadar susut pengeringan 3,6817%.